Minimally invasive perinatal and pediatric autopsy with laparoscopically assisted tissue sampling: feasibility and experience of the MinImAL procedure. (5th November 2019) - Hutchinson, J. C.; Shelmerdine, S. C.; Lewis, C.; Parmenter, J.; Simcock, I. C.; Ward, L.; Ashworth, M. T.; Chitty, L. S.; Arthurs, O. J.; Sebire, N. J.
ABSTRACT: Objective: Less invasive autopsy techniques in cases of fetal or infant death have good acceptability among parents, but the published sampling adequacy in needle biopsy studies is generally poor. Minimally Invasive Autopsy with Laparoscopically assisted sampling (MinImAL) has the potential to increase the diagnostic yield of less invasive autopsy by improving the quality and quantity of tissue samples obtained, whilst permitting visualization, extraction and examination of internal organs through a small incision. The aim of this study was to present the findings of our experience with the MinImAL procedure in cases of fetal, neonatal and pediatric death. Methods: This was a retrospective analysis of 103 prospectively recruited unselected cases of fetal, neonatal or pediatric death that underwent the MinImAL procedure at a tertiary referral center over a 5‐year period. Following preprocedure 1.5‐T whole‐body postmortem magnetic resonance imaging, MinImAL autopsy was performed. Procedure duration, sampling adequacy and cause of death were assessed. Chi‐square analysis was used to compare the 'unexplained' rate of intrauterine deaths in the cohort with that in a previously published cohort of > 1000 cases of intrauterine death examined by standard autopsy. Results: MinImAL autopsy was performed successfully in 97.8% (91/93) of the cases undergoing a complete procedure. There was a satisfactory rate of adequate histological sampling in most major organs; heart (100%, 91 cases), lung (100%, 91 cases), kidney (100%, 91 cases), liver (96.7%, 88 cases), spleen (94.5%, 86 cases), adrenal glands (89.0%, 81 cases), pancreas (82.4%, 75 cases) and thymus (56.0%, 51 cases). Procedure duration was similar to that of standard autopsy in a previously published cohort of intrauterine deaths. The unexplained rate in stillbirths and intrauterine fetal deaths that underwent MinImAL autopsy was not significantly different from that following standard autopsy. Conclusions: The MinImAL procedure provides good histological yield from major organs with minimal cosmetic damage and can be learned by an autopsy practitioner. The MinImAL procedure is an appropriate minimally invasive alternative for the investigation of perinatal and pediatric deaths in which consent to full autopsy is withheld, and may have applications in both high‐ and low/middle‐income settings. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.